The Implications of Stripping Immunities of Heads of States on State Cooperation and the Effectiveness of Trial (Strathmore Law Review, 2016)
The development of international criminal law in the last seven decades has seen a gradual erosion of the integrity of immunities for heads of states. The journey from Nuremberg to The Hague has resulted in a permanent international criminal court. Article 27(2) of the Rome Statute of the International Criminal Court (the Rome Statute) disregards immunities as an effective bar to the jurisdiction of the International Criminal Court (ICC). Heads of states have been stripped of their ‘invisibility cloak’ from international criminal prosecutions. The Rome Statute places its reliance on the situation state’s authorities to cooperate with the ICC in its investigation and prosecution of crimes. A special tension is noticeable in circumstances where an incumbent head of state is accused at ICC while his or her state is placed under the general cooperation obligation. This tension is clearly manifest in the two criminal processes against Uhuru Kenyatta and Al Bashir. Bearing in mind the significant political muscle a sitting head of state wields in their state, it is quite likely that their state’s authorities will be very reluctant to discharge their cooperation obligations. The prosecution of sitting heads of states remains a challenge. Is it time to rethink the structure of the ICC or the implementation of the Statute?